2014
DOI: 10.1590/abd1806-4841.20142792
|View full text |Cite
|
Sign up to set email alerts
|

Sports-related dermatoses among road runners in Southern Brazil

Abstract: BACKGROUND Road running is a growing sport. OBJECTIVES: To determine the prevalence of sports-related dermatoses among road runners. METHODS Cross-sectional study of 76 road runners. Assessment was performed by means of a questionnaire, interview, and clinical examination. The chi-square and linear trend tests were used for analysis. RESULTS Most athletes were men (61%), aged 38±11 years, who ran mid- or long-distance courses (60.5%) for 45 to 60 minutes (79%), for a total of 25-64 km (42.1% ) or more than 65 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 24 publications
(62 reference statements)
1
10
2
Order By: Relevance
“…In sum, after heel touch, the pressure on the first toe pad of subjects with PN increased more rapidly and was more concentrated than that in subjects without PN. This may explain why athletes who need to kick the ground strongly frequently experience PN . However, our data conflict with previous reports wherein authors have demonstrated that the pressure on the first toe of subjects with PN was lower than that of those without PN, and that subjects with PN experienced peak pressure on the metatarsal area .…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In sum, after heel touch, the pressure on the first toe pad of subjects with PN increased more rapidly and was more concentrated than that in subjects without PN. This may explain why athletes who need to kick the ground strongly frequently experience PN . However, our data conflict with previous reports wherein authors have demonstrated that the pressure on the first toe of subjects with PN was lower than that of those without PN, and that subjects with PN experienced peak pressure on the metatarsal area .…”
Section: Discussioncontrasting
confidence: 99%
“…This may explain why athletes who need to kick the ground strongly frequently experience PN. 8 However, our data conflict with previous reports wherein authors have demonstrated that the pressure on the first toe of subjects with PN was lower than that of those without PN, and that subjects with PN experienced peak pressure on the metatarsal area. 2,3 This discrepancy may be attributable to the fact that we only studied female subjects with PN and used different devices for analyses.…”
Section: Discussioncontrasting
confidence: 99%
“…Traumatic onychomadesis is generally associated with obvious, sometimes dramatic trauma, such as repetitive friction from long-distance running, wrist and arm fracture, or fingertip crush injury [2,10]. The use of ill-fitting, closed-toe shoes with a narrow toe box in the winter is a logical source of recurrent, seasonal toenail trauma.…”
Section: Discussionmentioning
confidence: 99%
“…Although SARS‐CoV‐2 virus is not dermatotropic primarily, this has affected everyone and caused various dermatoses. Several dermatoses have been reported due to jogging, such as acne, friction/sweat dermatitis, pressure dermatitis, cheilitis, and irritant dermatitis 2 . We report a preliminary data of joggers who experienced dermatoses during this time of the COVID 19.…”
Section: Variables Number (N) Percentage (%)mentioning
confidence: 94%
“…Several dermatoses have been reported due to jogging, such as acne, friction/sweat dermatitis, pressure dermatitis, cheilitis, and irritant dermatitis. 2 We report a preliminary data of joggers who experienced dermatoses dur- The most common noted dermatoses was facial acne (54.55%) followed by friction dermatitis (45.46.5%) after which pressure dermatitis was seen in (36.36%) and chelitis and irritant dermatitis which were (27.27%) and (18.18%). However, the most common symptom was pruritus (72.73%), while the most observed sign was erythema (53.55%).…”
mentioning
confidence: 95%